Digital transformation in Erasmus Mobility Application Procedures: Transforming a paper-based workflow into an online system - Tylšar, Oliver (2019)
In the process of organising exchange mobility, students and higher education staff members must conclude trilateral Learning Agreements that are the basis for the recognition of academic qualifications obtained abroad. According to the PRIME survey, conducted by the Erasmus Student Network in 2010-11, while Learning Agreements (LA) documents may be considered essential to an adequate organisation of credit mobility, there are several issues that hamper their preparation. In fact, the interlocutors involved are often not clearly defined, the information needed to build the agreements is rarely available online and in up to 75% of the cases, students need to change their learning agreements after their arrival at the receiving Higher Education Institutions (HEI), usually due to changes in their study plans abroad. Furthermore, as the process is mainly paper-based, it is error prone and time consuming. This paper describes the project developed by the authors, including two Postgraduate Erasmus students, conducted in the context of Erasmus+ Student Mobility for Placements (SMP) at Portucalense University (UPT). The aim of the project is to develop a web-based software platform to automate the process of submitting applications for UPT students exchange and UPT academic and non-academic staff exchange (STA and STT) within the Erasmus+ programme. The application was termed “ErasmusOnlineLAapp” and addresses the dematerialization of the process of organising exchange mobility, transferring a paper-based workflow, which is reliant on timely postal deliveries for signature purposes, into an online system that will allow students to gain considerable time when preparing their studies abroad and induce a greater degree of flexibility and efficiency when needing to revise the Learning Agreement.